'An important contribution to the allied war effort': Canadian and North Atlantic intelligence on German POWs, 1940–1945. Issue 2 (23rd February 2019) - Turcotte, Jean-Michel
ABSTRACT: This article examines inter-allied efforts to collect, categorize and analyse material gathered from the thousands of German prisoners of war (POWs) in their hands during the Second World War. The different information gathered from enemy captives was valuable to British, Canadian and American intelligence services, helping them to evaluate morale of 'Hitler's soldiers', to improve the security of their camp networks and to understand National Socialism ideology. Often viewed as a primarily British-American operation, POW intelligence also involved Canadian authorities. This article argues that Canada, far from being a secondary actor, had a central role within this transatlantic network.